A marginal structural model for estimation of the effect of HIV positivity awareness on risky sexual behavior. Issue 2 (3rd July 2022) - Twabi, Halima S.; Manda, Samuel O. M.; Small, Dylan S.; Kohler, Hans-Peter
Abstract : In this paper, a Marginal Structural Model (MSM) with inverse probability of treatment weights was used to estimate the causal effect of HIV positivity awareness on condom use and multiple sexual partners using data from the Malawi Longitudinal Study of Families and Health (MLSFH). Cumulative awareness of HIV positivity was measured as the number of times an individual was aware of their positive HIV status. Awareness of HIV positivity was associated with increased condom use (OR=2.22, 95%: (1.79, 2.75)). Only among women was it associated with multiple sexual partners (OR=1.76, 95%: (1.36, 2.28)). The use of MSM (over standard regression models for repeated measures) should be encouraged as it is more suited for assessing the cumulative treatment effects while controlling for time-varying confounders in longitudinal studies. There is a need to up-scale interventions that promote HIV testing, awareness of HIV status, and prevention of HIV transmission.